Utilization of Light Emitting Diode (LED) lamp with difference color as attractor for fixed lift net as small scale fisheries in Makassar Strait, Indonesia. Issue 1 (September 2020) - Sudirman; Musbir; Kurnia, M
Abstract: Use of light for the some types of fisheries has been one of the most advance and successful methods to control fish to capture process. Several fishing technology operated in Indonesia waters, used of light as attractor for catching of the small pelagic fish. A lot of typed of lamps used by the fisherman, like incandescent lamp, florescent lamp, mercury lamp and metal haline lamp. In the development of technology, now the some company, was introduce new lamp typed with environmentally friendly technology called Light Emitting Diode (LED) lamp. Research about utilization of Light Emitting Diode (LED) lamp with different color and color combination of fixed lift net was conducted in Makassar Strait during the May- November 2018 and March – September 2019. The research aimed was to determine the best effectively color of LED can use as attractor for pelagic fish in fixed lift net in Makassar Strait. Experimental fishing was conducted in one unit commercial fixed lift net with bamboo platform size 15 m x 15m in Pangkep regency Makassar Strait. Data were obtained at every fishing operation by examining the catch species, total catch, by-catch and discard species every hauling time. In 2018 there are three color LED namely white, yellow and blue color. Experimental fishing for 30 hauling time for each color of LED in 2018 and 35 time for each LED in 2019 with color combination. Data were collected two time a week during. Fixed lift net did not operated during the full month (one week a month). Total lighting power of 374 W, with 16 total unit LED lamps was setting under the lift net flatform. The result showed that Light Emitting Diode (LED) is effective as attractor in fixed lift net fisheries to utilization of small pelagic species in coastal area. There are 25 species captured of the fixed lift net during the experimental fishing in Makassar. There are five dominant and commercial species, there called main species are Anchovies ( Stolephorus sp), Sardine ( Sardinella sp ), Pony fish ( Equulites sp), squids ( Loligo sp ), and Big eye scad ( Selaroides sp ). White color and combination of white-blue – yellow color is preference color for small pelagic species.